Estudo in vitro de infecção polibacteriana das membranas corioamnióticas: modulação da resposta imune na interface materno-fetal. - Bento, Giovana Fernanda [UNESP] (2020)
Problem: Preterm labor (PTL) is considered one of the main Obstetric Clinic problems that occurs in almost 10% of all pregnancies in the world. Polybacterial invasion and inflammation of the amniotic cavity is a common scenario in PTL that results in host inflammatory response. We aimed to evaluate the production and kinetics of inflammatory mediators in in vitro models of fetal membrane coinfection with mycoplasmas and other bacteria species. Method of Study: Fetal membranes collected from healthy pregnancies by c-section were stimulated with heat-killed genital micoplasmas (Mycoplasma hominis, Ureaplasma parvum), Streptococcus agalactiae and Fusobacterium nucleatum, alone or in combination. Culture supernatants were collected at five different time-points: 0h, 6h, 12h, 18h, and 24h. Cytokines (IL-6, IL-8, IL-10, and TNF-α) were measured in the culture medium by ELISA. Results: Stimulation by genital mycoplasmas, alone or in combination, increased the levels of proinflammatory cytokines, whereas F. nucleatum and S. agalactiae did not produce significant differences. Highest levels of TNF-α were detected at time-point 6 and 12, in contrast to IL-10, which peaks appeared at time-point 18h. Conclusions: M. hominis and U. parvum sustain a proinflammatory response in the fetal membranes in vitro alone or in combination, but did not respond in the same way in the presence of other bacteria. Therefore, the polymicrobial infection results in a proinflammatory pattern and a balance of anti-inflammatory response.